financial,Labour,Certified HUMAN RECOURSES STRENGTHENING FINANCIAL MANAGEMENT THROUGH TECHNICAL COMPETENCE CERTIFIED - admin admin (POLITEKNIK PIKSI GANESHA, 2018)
At the beginning of 2016, was inaugurated jointly by the 10 ASEAN countries, the ASEANEconomic Community. A condition where, goods, services and labor-free entry into each of the 10ASEAN countries. One of the areas of th e collective agreement is accounting.Accounting or finance, not just workers with a university degree, but there are graduates ofvocational and diploma are also competing in accordance with the formal education andcompetency. However, their position is not in accordance with the competence at the time of theirschools and their competence was also not in accordance with the standards of competence.This, a dilemma for the organizers of the competency test ie Accounting Technician CompetencyCertification Institute Bond'09, at the time of the company / industry professionals need them, butthe availability of competent personnel can not be sufficient. Because a lot of unemployment isincreasing every year of vocational school graduates, many graduates of vocational competing notwith their competence, but with modest jobs available. In the author's data collection usinginterviews, observation and documentation. The population is only a sample of some of theAccounting Technician Competency Test Points are TUK LKP SWK Computers that are inCilacap. In organizing the competency test in TUK are still very few competent.